Modulation of Agrin and RhoA Pathways Ameliorates Movement Defects and Synapse Morphology in MYO9A-Depleted Zebrafish - Emily O’Connor; George Cairns; Sally Spendiff; David Burns; Stefan Hettwer; Armin Mäder; Juliane Müller; Rita Horvath; Clarke Slater; Andreas Roos; Hanns Lochmüller (Cells, 2019)
Congenital myasthenic syndromes (CMS) are a group of rare, inherited disorders characterised by impaired function of the neuromuscular junction (NMJ). This is due to defects in one of the many proteins associated with the NMJ. In three patients with CMS, missense mutations in a gene encoding an unconventional myosin protein, MYO9A, were identified as likely causing their disorder. Preliminary studies revealed a potential involvement of the RhoA/ROCK pathway and of a key NMJ protein, agrin, in the pathophysiology of MYO9A-depletion. In this study, a CRISPR/Cas9 approach was used to generate genetic mutants of MYO9A zebrafish orthologues, myo9aa/ab, to expand and refine the morphological analysis of the NMJ. Injection of NT1654, a synthetic agrin fragment compound, improved NMJ structure and zebrafish movement in the absence of Myo9aa/ab. In addition, treatment of zebrafish with fasudil, a ROCK inhibitor, also provided improvements to the morphology of NMJs in early development, as well as rescuing movement defects, but not to the same extent as NT1654 and not at later time points. Therefore, this study highlights a role for MYO9A at the NMJ, the first unconventional myosin motor protein associated with a neuromuscular disease, and provides a potential mechanism of action of MYO9A-pathophysiology.